Congenital and acquired mitochondrial disorders of the central nervous system - V. V. Nikitina; A. N. Pravdina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
Clinical presentations of disorders of the nervous system manifest in young and middle-aged patients with congenital and acquired mitochondrial dysfunctions and cognitive disorders manifest in patients with mitochondrial diseases more often. Nowadays the effective methods of initial diagnosing of these conditions are neurological and neuropsychological examination of patients, using of biochemical markers of mitochondrial diseases: the indices of lactate, total homocysteine in plasma and liquor. Neuro-visual study (Magnetic resonance imaging of the brain, MR spectroscopy, tractography, diffusion-weighted magnetic resonance imaging of the brain, mitochondrial DNA typing) is actually used for the differential diagnosing of mitochondrial diseases with other disorders that are accompanied by demyelinating disorders.